Auditoria de Sistemas Virtual a un Sistema de Gestión Documental de una Entidad Gubernamental (2021)
The main objective of this work is to propose a virtual systems audit methodology to audit a document management system of a governmental entity. The research has a methodological design with a qualitative approach, descriptive and propositive scope with an analytical method. For data collection, the documentary method was used, which was made from the analysis of the ISO19011:2018 standard, the ISO 30300 series of standards, the legal regulation of document management systems of public entities in Colombia and in general the published research on systems auditing. The document management system of the Departmental Comptroller's Office of Sucre was taken as a sample. The results show that the methodology to audit a management system virtually should be subject to the phases of planning, execution and results, which are applied virtually with the use of information and communication technologies. This paper presents a proposal to perform a virtual audit of the document management system of a government entity in accordance with ISO 19011:2018 and civil service standards. It is concluded that the virtual systems audit to document management is executed in three phases that in turn establish activities to evaluate the modules, controls and thus know the operational effectiveness of the system according to the objectives of the entity.